1972
DOI: 10.1021/j100663a008
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of (n,.gamma.)-activated hot iodine-128 reactions in gaseous methane and halomethanes. Energy Degradation factor

Abstract: It was found in a systematic study of 128I reactions activated by radiative neutron capture in various gaseous halomethanes that the formation of 128I-labeled organic products proceeds entirely by hot (requiring excess kinetic energy to occur) reactions. This is unlike the reactions of 128I with CH4 where the organic product CH8128I was formed not only by hot 128I atoms but by thermal ion-molecule reactions involving 1+ in the 'D2, 8P0, 8Pi, and 3P2 states. In the various halomethane systems only two 128I-labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
2

Year Published

1973
1973
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 1 publication
3
17
0
2
Order By: Relevance
“…Unlike the condensed-state studies [3,4] which showed that the total (n, 7)-activated yields were lower than the total (I. T.)-activated yields, our results from gas phase studies (see Table 2) showed consistently that the hot yields of 130 I + 130m I activated by radiative neutron capture were consistently higher than hot (I. T.) activated 130 I yields. This is consistent with the fact that (η, γ), activated 130 I species are formed with larger kinetic energies [12] than l30 I activated by (I. T.). Thus the (η, γ)-activated 130 I + 130m i has available the full reaction energy range in which to undergo reactive collision.…”
Section: Discussionsupporting
confidence: 88%
“…Unlike the condensed-state studies [3,4] which showed that the total (n, 7)-activated yields were lower than the total (I. T.)-activated yields, our results from gas phase studies (see Table 2) showed consistently that the hot yields of 130 I + 130m I activated by radiative neutron capture were consistently higher than hot (I. T.) activated 130 I yields. This is consistent with the fact that (η, γ), activated 130 I species are formed with larger kinetic energies [12] than l30 I activated by (I. T.). Thus the (η, γ)-activated 130 I + 130m i has available the full reaction energy range in which to undergo reactive collision.…”
Section: Discussionsupporting
confidence: 88%
“…The model appears insensitive to variation in the initial energy sampling (Energy Gaussian). It is interesting to note that this appears in agreement with kinetic theory [7][8][9] even though the iodine-128 activation is in violation of Assumption la of the theory [38]. However, it has been previously demonstrated [20] that kinetic theory relationships may be obtained in systems known to be in violation of some kinetic theory requirements.…”
Section: Resultssupporting
confidence: 72%
“…The cell size and location of the acetylenes were variable and adjusted to vary the effect of a collapsing molecular environment on the system. The locations and spacings of the acetylene were chosen [38] to mimic actual physical conditions. For simplicity, the acetylene molecules were "fixed" since their thermal motions were much smaller than the translational motions of the iodine.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the characteristics of 128 I compound nucleus and its subsequent de-excitation through photon emission or electron conversion and the associated recoil spectra [6] have made the subject interesting. The spin and parity i.e.1 + [7] of the ground state of 128 I is different from the spin and parity of 127 I i.e.…”
mentioning
confidence: 99%